Learning obstacles in solving story problems on probability for vocational high school students - Sartika, Nenden Suciyati; Mustika, Siti Mega; Sahrudin, Asep; Meika, Ika; Mauladaniyati, Ratu; Yunitasari, Ika (Universitas Hamzanwadi, 2024)
This research aims to determine and obtain actual data on the types of epistemological learning obstacles in solving probability story problems. This study was motivated by the low learning outcomes of students in solving probability story problems. The research uses a qualitative descriptive method with data collection techniques, including written tests, interviews, and documentation. Based on the analysis of the written test, interviews, and documentation data, it was found that out of 20 students who took the learning obstacle test, 11 scored below 60. The percentage of students who scored below the minimum completion criteria was 55%. These obstacles include errors in understanding the problem concept, errors in selecting and using solution procedures, errors in writing answers, and errors in operational techniques. It indicates that half of the students who took the learning obstacle test on probability story problems still experience learning obstacles, particularly epistemological obstacles, in solving such issues. It is reinforced by analysis and in-depth interviews with three vocational students that these students still participate in epistemological obstacles ranging from conceptual, procedural, and technical operational obstacles.